(untitled) (Global Journal of Science Frontier Research, 2015)
Mull-Arg. and P. muellerianus (O. Ktze) Excel belonging to the family of Phyllanthaceae were extracted, purified, PCR amplified and sequenced using plastid Ribulose -1,5 bisphosphate carboxylase large chain (rbcL a) and Maturase K (matK) genetic marker to identify unknown Phyllanthus species. The plastid region revealed that the Phyllanthus species were able to be amplified optimally for sequencing. The results of the nucleotide sequences were further compared on Basic Local Alignment Sequence Tool (BLAST) on Gen Bank and Bold Systems for validation. Results revealed that the closely related species, P. niruroides Mull_Arg. and P. odontadenius Mull-Arg. had no DNA record to separate them on both GenBank and Bold Systems using both rbcL and matK gene regions while P. amarus Schum and Thonn and P. urinaria Linn. were clearly compatible with other works. P. muellerianus (O. Ktze) Excel was only compatible with other works using matK gene region but none for rbcL.